PENERAPAN METODE INKUIRI DALAM PEMILIHAN TOPIK TULISAN AKADEMIK - Zulmy Faqihuddin Putera; Nurul Shofiah; Tutuk Widiowati (Universitas Pendidikan Ganesha, 2023)
The aim of this research is to explain the procedure for applying the inquiry method in the research topic selection process and to present students' perceptions of inquiry-based learning in research topic selection. The method used is classroom action research. The research data source is 24 seventh-semester students of D4 Civil Engineering at the State Polytechnic of Malang. The research instruments are observation guidelines and a questionnaire on student responses. The results show that (1) the inquiry learning procedure on research topic selection material has six stages: orientation, problem formulation, hypothesis formulation, data collection, conclusion formulation, and reflection, and (2) students' perceptions of inquiry learning indicate a positive effect on determining research topics. Thus, inquiry-based learning in the research topic selection process is recommended as a means to enhance students' academic writing skills because this method combines activity-oriented learning and logical arguments. Keywords : Inquiry, research topic, topic selection, learning. Abstrak Tujuan penelitian ini untuk menjelaskan prosedur penerapan metode inkuiri dalam proses pemilihan topik penelitian serta memaparkan persepsi mahasiswa terhadap pemebelajaran inkuiri pada pemilihan topik penelitian. Metode yang digunakan adalah penelitian tindakan kelas. Sumber data penelitian yakni 24 mahasiswa semester tujuh D4 Teknik Sipil Politeknik Negeri Malang. Instrumen penelitian berupa pedoman observasi dan kuisioner tentang respon mahasiswa. Adapun hasil penelitian menunjukkan bahwa (1) prosedur pembelajaran inkuiri pada materi pemilihan topik penelitian memiliki enam tahapan yaitu orientasi, merumuskan masalah, merumuskan hipotesis, mengumpulkan data, merumuskan kesimpulan dan refleksi dan (2) persepsi mahasiswa terhadap pembelajaran menunjukkan secara positif dapat membantu menentukan topik penelitian. Dengan demikian, pembelajaran inkuiri dalam proses pemilihan topik penelitian disarankan sebagai sarana untuk meningkatkan keterampilan penulisan akademik mahasiswa karena metode tersebut menggabungkan pembelajaran berorientasi aktivitas dan argumen logis.